2017
DOI: 10.1175/jcli-d-16-0903.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Eight Current Reanalyses in Simulating Land Surface Temperature from 1979 to 2003 in China

Abstract: Land surface temperature Ts provides essential supplementary information to surface air temperature, the most widely used metric in global warming studies. A lack of reliable observational Ts data makes assessing model simulations difficult. Here, the authors first examined the simulated Ts of eight current reanalyses based on homogenized Ts data collected at ~2200 weather stations from 1979 to 2003 in China. The results show that the reanalyses are skillful in simulating the interannual variance of Ts in Chin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 75 publications
7
35
0
Order By: Relevance
“…1 and Table 2). Similar biases in T a within various regions worldwide have been widely reported by previous studies (Mao et al, 2010;Pitman and Perkins, 2009;Reuten et al, 2011;Wang and Zeng, 2012;Zhou et al, 2017;Zhou and Wang, 2016b). However, we found that the spatial patterns in the differences in T a are well correlated with the elevation differences between models and stations, as reflected by correlation coefficients (r) of 0.85 to 0.94 (Figs.…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…1 and Table 2). Similar biases in T a within various regions worldwide have been widely reported by previous studies (Mao et al, 2010;Pitman and Perkins, 2009;Reuten et al, 2011;Wang and Zeng, 2012;Zhou et al, 2017;Zhou and Wang, 2016b). However, we found that the spatial patterns in the differences in T a are well correlated with the elevation differences between models and stations, as reflected by correlation coefficients (r) of 0.85 to 0.94 (Figs.…”
Section: Resultssupporting
confidence: 89%
“…In addition, we replicate the procedures above for the sparsely distributed stations over western China and the Tibetan Plateau. The PMTred algorithm and the QM adjustment have recently been used successfully to homogenize climatic time series (Aarnes et al, 2015;Tsidu, 2012;Dai et al, 2011;Siswanto et al, 2015;Wang and Wang, 2016;Zhou et al, 2017). As such, the significant breakpoints are detected and adjusted at a confidence level of 95 % at 1092 of the 2193 …”
Section: Methods Used To Homogenize the Observed Time Seriesmentioning
confidence: 99%
See 3 more Smart Citations